Association Between Coagulation Fibrinolysis Markers and Severity in Patients with COVID-19 - Takuya Iwamoto MT; Yuki Hatayama PhD; Noriko Yamashita MT; Hitomi Ichikawa MT; Koji Kawamura MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Introduction Thrombosis is a major complication of COVID-19. D-dimer (DD) is an important coagulation fibrinolysis marker in COVID-19 and has been extensively studied. However, very little is known about the role of other fibrinolysis markers, plasmin-plasmin inhibitor complex (PIC), and fibrin monomer complex (FMC) in COVID-19. This study investigated and compared the associations of DD, PIC, and FMC with COVID-19 severity. Methods Archived plasma samples from patients with COVID-19 (n = 50) were assessed for DD, FMC, and PIC levels. We compared the levels between patients with mild (n = 36) and moderate (n = 14) COVID-19 and evaluated their correlation with other COVID-19 severity markers, including lactate dehydrogenase (LD), serum albumin (Alb), C-reactive protein (CRP), and neutrophil-lymphocyte ratio (NLR). Results Patients with moderate COVID-19 had significantly higher DD and PIC levels than those with mild disease, while FMC levels were comparable. DD and PIC levels significantly correlated with LD, Alb, and NLR. Additionally, PIC levels significantly correlated with CRP levels. However, FMC levels correlated only with Alb but not with LD, NLR, or CRP. Conclusions COVID-19 severity was significantly associated with PIC and DD levels but not with FMC levels. PIC was the variable with the most clearly significant difference between patients with moderate disease and those with mild disease, highlighting its potential as an indicator of coagulation and fibrinolysis imbalance in patients with COVID-19. Further studies with larger sample sizes and more diverse severity groups are required to confirm these findings.